PENGARUH KENAIKAN TEMPERATUR LINGKUNGAN TERHADAP KONSUMSI ENERGI LISTRIK PADA SISTEM TATA UDARA - Sumardi, Kamin (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract Indesigning air conditioning system, global warming effect within a region isa very important factorbecause itcanaffect theperformanceor the efficiency and the electricityconsumptionof theair conditioning system. The increase in outsideor environment willincrease theheat loadthatmust becontrolled by the air conditioning system. This studyis aimedtoanalyze theincrease of outsideairtemperatureor the environment inthe City ofBandung, West Java, Indonesia on theperformance ofthe air conditioning system andelectricenergyconsumption. Resultsof this studyindicatethatan increase inoutsideor environment air temperaturebyr1oFreducethe cooling power (refrigerating effect) by0.5Btu/ lb, in average and increases thetheoreticalcompressorpower by 0.39Btu/lb in average. The increase in outside air temperature by 1oF also decreases the Coefficient ofPerformance (CoP)in averageby 0.3; decrease the refrigerantcirculationinthe systemin average by 0.025lb/ton-min, andraises electricenergyconsumptionin average by 26.38watts/ton or0.035HP/ton.
Keywords: Key word: temperature raise, electrical energy consumption, efficiency